Cardiac involvement in myotonic dystrophy - Koroush Khalighi; Archana Kodali; Suman B. Thapamagar; Stanley R. Walker (Greater Baltimore Medical Center, 2015)
Background: Myotonic dystrophy (DM) is an inherited progressive muscle disorder caused by defects in muscle proteins. As the incidence of this condition is low, not many are familiar with the multisystem involvement. At times, cardiac disease may even be the predominant manifestation in the form of arrhythmias, conduction defects, and cardiomyopathies. The progression of the disease can lead to sudden, unpredictable death. Thus, it is important to identify this subgroup and treat accordingly. Objective: To identify patients with DM and assess their risk for sudden cardiac death. Methods: Nine patients previously diagnosed with muscular dystrophy were evaluated by cardiologists for various reasons, from a general follow-up to cardiac arrest. All of them had electrocardiograms (EKG) and 2-D echocardiograms, and seven of them had further electrophysiological (EP) studies. Results: Of the nine patients with DM, eight had EKG evidence of conduction abnormalities ranging from first-degree heart block to complete heart block. Of the seven who had EP studies, five had inducible ventricular tachycardia requiring immediate cardioversion and implantable cardioverter defibrillator (ICD) implant. Two of them underwent permanent pacemaker placement due to complete heart block and infra-Hissian block. The remaining two patients opted for a conservative approach with yearly EKG monitoring. Conclusion: Because one-third of the cardiac deaths in patients with DM are sudden, there is a strong need to identify these patients and intervene in those at high risk. Prophylactic pacemaker placement is recommended even in those with minimal conduction system abnormality. However, the common practice is to identify patients at high risk of conduction abnormalities by EP studies and then provide them with prophylactic invasive strategies.